2015 IEEE 2nd World Forum on Internet of Things (WF-IoT) 2015
DOI: 10.1109/wf-iot.2015.7389101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobility on the IoT MAC infrastructure: IEEE 802.15.4e TSCH and LLDN platform

Abstract: Abstract-Realizing the target of high reliability and availability is a crucial concept in the IoT context. Different types of IoT applications introduce several requirements and obstacles. One of the important aspects degrading network performance is the node mobility inside the network. Without a solid and adaptive mechanism, node mobility can disrupt the network performance due to dissociations from the network. Hence, reliable techniques must be incorporated to tackle the overhead of node movement. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Mobility Models & Handover -The mobility is an important aspect of performance degradation in a mobile environment. The fast-moving vehicles or devices can very rapidly disassociate from the network [46]. Therefore, data loss and re-transmissions decrease overall network performance/efficiency.…”
Section: A Design Components and Utilitiesmentioning
confidence: 99%
“…Mobility Models & Handover -The mobility is an important aspect of performance degradation in a mobile environment. The fast-moving vehicles or devices can very rapidly disassociate from the network [46]. Therefore, data loss and re-transmissions decrease overall network performance/efficiency.…”
Section: A Design Components and Utilitiesmentioning
confidence: 99%
“…The majority of these studies provide little by way of practical evaluation and rely heavily on simulation and analytical analyses [11], [13], [14], [15], [16], [17], [18]. It has been found that traditional communications protocols for WSNs tend to perform poorly in practice [19], and researchers have begun to design bespoke protocols that specifically cater to aerial mobility. Qin et al designed an application protocol for a mobile sink to reliably collect data with moderate UAV speeds [1].…”
Section: Related Workmentioning
confidence: 99%
“…To adapt for mobility, Al-Nidawi and Kemp proposed the MTSCH scheme that focuses on reducing the latency incurred by the association and disassociation process [25]. They compared the impact of mobility between TSCH mode and low latency deterministic (LLDN) mode, described in [19]. The assumptions on mobility pattern and the probabilistic approach, however, constrain the usefulness of the method.…”
Section: Related Workmentioning
confidence: 99%
“…Every DODAG is formed according to the defined Objective Function (OF) which determines the routing metrics that will be used for selecting the preferred parent. Many applications require some of the nodes to be mobile which creates an extra challenge to routing especially when nodes move at high speeds or in an unpredictable pattern [3][4] [5]. RPL was originally designed for static networks but there are some efforts that proved it can be used for some mobile WSNs with a few alterations and enhancements [6].…”
Section: Introductionmentioning
confidence: 99%